Performance of Fe3O4@SiO2 as the recyclable heterogeneous catalyst in the bisphenol A recovery from polycarbonate wastes. Issue 2 (May 2019) - Emami, Samira; Alavi Nikje, Mir Mohammad
Received polycarbonate wastes from the used optical and digital optical disk (CDs and DVDs) were chemically recycled into bisphenol A (BPA) in 100% recovery yield using diethylene glycol/water as a binary solvent system and Fe3 O4 @SiO2 as the heterogeneous catalyst at the convenient, green and eco-friendly conditions using conventional heating method. The recovered BPA was analyzed by spectroscopic methods and data compared by an authentic sample.